Influence of Vitamin C on Hematology of Pangasianodon hypophthalmus (Sauvage, 1878) Juveniles during pre and post-challenge with Aeromonas hydrophila (Chester, 1901) - Daniel, N.; Muralidhar, A. P.; Srivastava, P. P.; Jain, K. K.; Prasad, K. Pani; Anandan, R.; Manish, J. (Fishery Technology, 2018)
A 60-day feeding trial was conducted to know theeffect of vitamin C on the hematological responsesof Pangasianodon hypophthalmus juveniles duringpre- and post-challenge conditions with Aeromonashydrophila. A total of seven purified diets wereprepared with 0 (control), 17.5 (T1), 35 (T2), 70 (T3),175 (T4), 350 (T5) and 700 (T6) mg ascorbic acid(AA) equivalent per kg of diet, supplied as Lascorbyl-2-polyphosphate (LAPP) and fed to triplicategroup of P. hypophthalmus juveniles (meaninitial body weight: 3.23Â±0.01 g to 3.38Â±0.01 g) for60 days twice daily. After the feeding and afterchallenging with A. hydrophila, the haematologicalparameters were measured in P. hypophthalmusjuveniles. All haematological parameter values(except albumin-globulin ratio) viz., serum glucose,total protein, albumin, globulin, hemoglobin (Hb),total erythrocyte count (TEC), total white blood cellscount (WBC), hematocrit value (HCT) increasedsignificantly (p